Water governance disclosure: the role of integrated reporting in the food, beverage and tobacco industry. Issue 7 (5th October 2022) - Botha, Martin; Oberholzer, Merwe; Middelberg, Susanna Levina
Abstract : Purpose: The purpose of this paper is to investigate current practices of water governance disclosure in the food, beverage and tobacco industry and to determine whether the quality of disclosure has a positive association with integrated reporting (IR). Design/methodology/approach: A water governance disclosure index was developed that used content analysis to code the latest standalone social, environmental and sustainability reports or integrated reports of 49 companies in the food, beverage and tobacco industry. The selected companies are listed on three indices, the ASX, JSE and DJSI. This was followed by quantitatively testing the association between IR and the quality of water governance disclosure, as measured against the qualitatively developed index. Findings: It was found that the 18 IR companies' water governance disclosure quality significantly outperformed the 31 companies in the non-IR group, with a calculated index score of 71.67% and 40.97%, respectively. Research limitations/implications: The evidence indicates that IR is superior to non-IR water governance disclosure, and the study, therefore, contributes to the literature around the legitimacy theory by concluding that IR is supportive to companies to legitimise their being. Originality/value: The originality of this paper stems from the comparison of water governance disclosures between IR and non-IR firms. Considering that IR preparers outperformed companies in the non-IR group could provide insights to academics, regulators and reporting organisations that IR could be used to enhance water governance disclosure.